Analysis of Electrically Shorted and Open Cases on Love Waves Propagating in Piezoelectric Layer Embedded over a Fiber-Reinforced Substrate - Suparna Roychowdhury; Abhijit Pramanik; Mostaid Ahmed (Mechanics of Advanced Composite Structures)
The article incisively analyzes the impact of piezoelectricity on Love wave transmission in an inhomogeneous bi-layered structure consisting of smoothly embedded thin piezoelectric material bonded to a semi-infinite fiber-reinforced medium. By applying the variable-separable method, a general form of dispersion equations, analyzing the Love waves’ characteristics in electrically open and shorted cases of the piezoelectric material has been derived. The crux of the study lies in the fact that the presence of the prestresses in the upper layer and lower half-space along with elastic, piezoelectric, and permittivity coefficients lead the derived frequency relation to merge with the classical form of equations of the Love waves. The procured dispersion relation substantiates that the depth of the upper layer prestresses, and piezoelectricity coefficients play a guiding role in the transmission of Love waves. The numerical discussions and findings carry wider applications and may imply guidance of additive manufacturing of varied composite multi-materials for pre-stressed and microstructural configurations with partial and global dispersion properties